Crystal structure of a lipin/Pah phosphatidic acid phosphatase - Valerie I. Khayyo (Nature Portfolio, 2020)
Lipin/Pah phosphatidic acid phosphatases generate diacylglycerol to regulate triglyceride synthesis and cellular signaling. Here authors determine structures of Tetrahymena thermophila Pah2 and identify an N-terminal amphipathic helix essential for membrane association.